2018
DOI: 10.3390/nano8070491
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Oxidation Degrees of Graphene Oxide on P-Type and N-Type Si Heterojunction Photodetectors

Abstract: Oxygen-containing functional groups in graphene oxide (GO), a derivative of graphene, can widen the bandgap of graphene. In this study, we varied the amount of hydrogen peroxide used to prepare GO samples with different degrees of oxidation. Transmittance measurement, Raman spectroscopy, and X-ray photoelectron spectroscopy were used to completely characterize the change in oxidation degree. The effects of oxidation degree on p-type and n-type Si heterojunction photodetectors were compared. Notably, GO with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…This result demonstrates that the reduction process used in this work has tuned the energy gap of the GO-based material, so that decreasing the GO oxidation degree it is possible to reduce the energy gap 50 , 51 .…”
Section: Resultsmentioning
confidence: 71%
“…This result demonstrates that the reduction process used in this work has tuned the energy gap of the GO-based material, so that decreasing the GO oxidation degree it is possible to reduce the energy gap 50 , 51 .…”
Section: Resultsmentioning
confidence: 71%
“…The D band reflects the formation of disorders and defects including grain boundaries and heteroatoms introduced into the graphitic structure. A large integral area ratio of D band to G band, that is, I D / I G , somehow testifies a high degree of oxidation of GO . The X-ray photoelectron spectroscopy (XPS) survey spectrum reveals the characteristic peaks for C 1s and O 1s (see Figure S1, Supporting Information).…”
Section: Resultsmentioning
confidence: 97%
“…A large integral area ratio of D band to G band, that is, I D /I G , somehow testifies a high degree of oxidation of GO. 25 The X-ray photoelectron spectroscopy (XPS) survey spectrum reveals the characteristic peaks for C 1s and O 1s (see Figure S1, Supporting Information). The high-resolution C 1s XPS spectrum can be deconvoluted into three Gaussian peaks centered at binding energies of 287.9, 286.6, and 284.5 eV, which can be assigned to CO, C−O, and C−C bonds within the GO structure, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The S2p 3/2 peak shifted from 99.63 eV to 99.81 eV, which could be due to a change in the conductivity type of silicon following P doping. The position of the Si2p peak in n-and p-type Si can differ by ~0.18 eV [48,49]. The preservation of such a shift after etching in the HF solution indicated that, unlike oxidation, doping occurred in the deep layers of silicon.…”
Section: The Surface Morphology and Structure Of Laser-doped N + P-simentioning
confidence: 99%